Durability of geopolymer stabilised compacted earth exposed to wetting–drying cycles at different conditions of pH and salt. (25th April 2022) - Ngo, Thanh-Phong; Bui, Quoc-Bao; Phan, Vu To-Anh; Tran, Huu-Bang
Highlights: The UCS of GSCE samples with Na2 SiO3 /NaOH ratio of 1.5 and 8% AAS had values in a range from 9.04 MPa to 10.06 MPa for the curing age from 14 to 180 days. The compressive and splitting tensile strengths of GSCE samples decreased when the w-d cycles increased, except in the case of the samples in the pH = 4 solution: both compressive and splitting tensile strengths of GSCE samples increased until 6 w-d cycles, then these parameters decreased in the further w-d cycles. SEM, XRD, and FTIR techniques were used to characterise the microstructure, mineralogical and chemical compositions of different samples. GSCE with 8% AAS could satisfy the high exigences in the case of severe conditions. Abstract: The paper presents an experimental study on the durability of geopolymer stabilised compacted earth (GSCE) samples exposed to various wetting–drying (w-d) cycles at different pH and salt concentration conditions. Compressive strength, splitting tensile strength, weight loss, and moisture content were determined after 1, 3, 6, 9, and 12 w-d cycles. The microstructure, mineralogical and chemical compositions were characterised by SEM, XRD, and FTIR techniques. The results showed that after 12 w-d cycles, all samples tested had compressive strengths higher than 4.5 MPa. This value was higher than the minimum value required by the standards. The samples exposed to the pH = 4 solution had the highest performance. The results show the potential application of GSCE in severe conditions.